الفساد المالي في دولة الكويت أطر محاربته وفق الشريعة والقانون - عازمي، ملفي محمد مجبل
The research problem goes around the issue of financial corruption that became a phenomenon that troubles the state. It also affects economic growth rates because of the absence of legitimate and legal frameworks to combat it. The researcher followed the qualitative method by relying on analyzing the formal reports; information and data gathered by some sort of means such as interviews and notes and evaluating the indicators of corruption during the last ten years in the State of Kuwait. This research aimed to identify the types of financial corruption’ its aspects, and effects in general and in the State of Kuwait in particular. It is also to identify the reasons beyond the spread of financial corruption as well as attempt to stop such a phenomenon (i.e., introducing practical solutions to fight it through activating the serious and strong penal laws of the Qur'an and Sunnah). The results indicated a high indicator of financial corruption in the State of Kuwait that started to increase during the last ten years. All theses aspects include money laundering, bypasses, manipulating the money of sovereign funds to invest in suspicious projects, the real-estate swindle, issues related to investing the money of the Public Institution of Social Insurance (retirement sums), and so on. The researcher developed a set of recommendations and proposals on both the penal and Sharia sides, including promoting religious speech in all forms of media, mosque, tribunes, and all religious institutions about the dangers of financial corruption to members and society. It is also by warning people about God punishment against every spoiler, activating the role of religious members in all attempts of the government to fight the financial corruption phenomenon in the state with definite adherence to the Islamic law principles in all financial dealings of the state, agreements and so on. Moreover, it is necessary to activate the extreme laws and penalties against perpetrators of financial corruption without exception.